San Josemaría, predicador de ejercicios espirituales a sacerdotes diocesanos (1938-1942). Análisis de las fuentes conservadas / St. Josemaría, retreat master for diocesan priests (1938-1942). Analysis of available sources - Nicolás Álvarez de las Asturias (Studia et Documenta)
The dedication of Josemaría Escrivá de Balaguer to preaching Spiritual Exercises and Retreats to Diocesan Clergy is almost completely centered on the period ranging from 1938 to 1942. In order to study this activity, use is made of the preaching outlines used as well as the numerous written testimonies of those who listened to the preaching. Commencing with a critical analysis of these documents, the objective is to establish the sources, structure and basic content of the preaching in addition to the most characteristic features.